A Microtremor Survey to Identify Seismic Vulnerability Around Banda Aceh Using HVSR Analysis - Andrean Vesalius Hasiholan Simanjuntak; Yusran Asnawi; Muksin Umar; Syamsul Rizal; Muhammad Syukri (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2020)
Abstract: Banda Aceh can be categorized as an earthquake-prone city because of the existence of two active segments namely Seulimeum and Aceh. Both segments are considered to provide great potential damage in the future. In this article, we conduct a microtremor survey in the Peukan Bada, sub-part of Banda Aceh city, to learn the vulnerability level and support disaster mitigation plan. A total of 20 sites were measured with a seismometer to record the seismic waveform. The waveform was recorded in 45 minutes with a sampling rate of 100 sps and has analyzed using the horizontal-vertical spectrum ratio (HVSR). The results obtained are the dominant parameters, such as the period with a range of 0 – 0.5s, frequency with a range of 0 – 6 Hz, seismicity vulnerability index with a range of 0.1 – 0.5. The result was relevant to the geological conditions of Peukan Bada that dominated by alluvial rocks and mud sediments. The level of vulnerability (Kg > 1.0) obtained is quite high and proportional to the soil type that can amplify the seismic waveform. The results obtained are expected to be a supporting study of disaster mitigation and understand the geological conditions of Banda Aceh in terms of seismic vulnerability.Abstrak: Banda Aceh dapat dikategorikan sebagai kota rawan gempa karena adanya dua segmen aktif yaitu Seulimeum dan Aceh. Kedua segmen tersebut bisa memberikan potensi kerusakan yang besar di masa mendatang. Pada tulisan ini, kami melakukan survei mikrotremor di Kecamatan Peukan Bada, salah satu sub-wilayah kota Banda Aceh, untuk mempelajari tingkat kerentanan dan mendukung rencana mitigasi bencana. Sebanyak 20 lokasi diukur dengan seismometer untuk merekam bentuk gelombang seismik. Gelombang direkam selama 45 menit dengan jumlah sampel 100 sps dan dianalisis menggunakan horizontal-vertical spectrum ratio (HVSR). Hasil yang diperoleh adalah parameter yang dominan yaitu periode dengan rentang 0 – 0,5s, frekuensi dengan range 0 - 6 Hz, indeks kerentanan kegempaan dengan rentang 0,1 – 0,5. Hasil tersebut relevan dengan kondisi geologi Peukan Bada yang didominasi oleh batuan aluvial dan endapan lumpur. Tingkat kerentanan (Kg > 1,0) yang diperoleh cukup tinggi dan sebanding dengan jenis tanah yang dapat memperbesar gelombang seismik. Hasil yang diperoleh diharapkan dapat menjadi pendukung kajian mitigasi bencana dan memahami kondisi geologi Banda Aceh dari segi kerentanan seismik.